Experiment on Corrosion Fatigue Life of Steel Strands under the Coupling Effects of Chloride Environment and Alternating Loads - Guowen Yao; Xuanrui Yu; Lifeng Gu; Yixing Jiang (Advances in Civil Engineering)
Corrosion pits will lead to local stress concentration on the surface of steel strands and even shorter fatigue life and worse mechanical properties of steel strands. In order to explore the corrosion mechanics of steel strands to predict the fatigue life, accelerated salt spray corrosion test is carried out to simulate the corrosion laws of steel strands and record the changes of the corrosion degrees during the experiment, considering the coupling effects of alternating loads and chloride environment. Besides, the impact of stress amplitudes on the corrosion degrees of steel strands is quantitatively studied by the corrosion weight loss, and corroded steel strands in experiment are graded according to the corrosion weight loss to test the mechanical properties, respectively; the results show that the corrosion weight loss and tensile strength of steel strands obey the exponential distribution, and the relationship with elongation is linear. In addition, the relationships between the stress concentration coefficient and the pit length, width, and depth are obtained; with the three-dimensional linear regression theory, the accuracy of the regression model is verified by t-value test, laying a foundation for predicting the corrosion life of the cables.